Digitalization of Behavioral Accounting as a Foundation for Managerial Decision Making - Gardi, Bayar; Ali, Rizwan (Metromedia, 2025)
Digital transformation has fundamentally reshaped the landscape of behavioral accounting, presenting both challenges and opportunities for enhancing managerial decision-making. Systems based on big data, artificial intelligence, and block chain enable more comprehensive information processing and enhance the accuracy of organizational behavior analysis. Nevertheless, the effectiveness of such integration is frequently hindered by behavioral barriers originating from users themselves. This study seeks to address two central issues: how digital technologies are transforming behavioral accounting practices to support managerial decisions, and how behavioral obstacles may affect the effectiveness of technological integration. Through a literature review of recent international publications, the analysis demonstrates that digital technologies can reduce cognitive biases, reinforce transparency, and improve objectivity in decision-making processes. However, resistance to change, limited digital literacy, distrust in technological systems, and technological anxiety have been shown to slow adoption and diminish the potential benefits of these advancements. Accordingly, the effectiveness of digital technology integration in behavioral accounting is determined not only by technical factors but is also significantly influenced by individual behavioral readiness and organizational culture. These findings underscore the critical importance of considering human factors in any digitization initiative, so that the designed systems can function as more strategic, adaptive, and sustainable decision-support instruments amid the dynamics of modern business.